1917
DOI: 10.1113/expphysiol.1917.sp000228
|View full text |Cite
|
Sign up to set email alerts
|

The Parathyroids:—tetania Parathyreopriva: Its Nature, Cause, and Relations to Idiopathic Tetany. Part V.: Guanidin and Methyl‐guanidin in the Blood and Urine in Tetania Parathyreopriva and in the Urine in Idiopathic Tetany

Abstract: The results may be summarised in the following table. Guanidin (and the methyl‐guanidins expressed as guanidin) in mg. per 1000 c.c.— A. Blood. Normal (average of 5) Dogs. Parathyroidectomy (average of 8). 1·0 8·7 B. Urine. Dogs. 0·25 (average of 6) 1·1 (average of 6) Children. Idiopathic tetany. (Average of 5 individuals—8 analyses.) (Average of 3 cases—13 analyses.) 0·12 Active tetany . 0·58 Latent tetany . 0·38 Recovery from tetany 0·12.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1926
1926
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…Monomethylguanidine (2) has been found in meat extracts, in muscle autolyzates, and in various tissues and biological fluids (Guggenheim, 1951). Its urinary excretion is increased in pathological conditions such as parathyroidectomy (Koch, 1913), newborn spasmophily (Burns and Sharpe, 1917) and adult tetany (Findlay and Sharpe, 1920). Elevated levels of methylguanidine and guanidine were also found in uremic sera (Carr and Schloerb, 1960;Giovannetti et al, 1973), and in the brain of mice with an epileptic disposition (Hiramatsu, 1980a).…”
Section: Guanidine and Its Derivativesmentioning
confidence: 99%
“…Monomethylguanidine (2) has been found in meat extracts, in muscle autolyzates, and in various tissues and biological fluids (Guggenheim, 1951). Its urinary excretion is increased in pathological conditions such as parathyroidectomy (Koch, 1913), newborn spasmophily (Burns and Sharpe, 1917) and adult tetany (Findlay and Sharpe, 1920). Elevated levels of methylguanidine and guanidine were also found in uremic sera (Carr and Schloerb, 1960;Giovannetti et al, 1973), and in the brain of mice with an epileptic disposition (Hiramatsu, 1980a).…”
Section: Guanidine and Its Derivativesmentioning
confidence: 99%
“…Because of the very small amounts of guanidine originally found by Burns and Sharpe [1916] and the lack of delicacy of the method used, these negative results could not be regarded as conclusive.…”
Section: Methodsmentioning
confidence: 98%
“…[Burns and Sharpe, 1916], then the injection of a relatively large dose of guanidine should again result in a large increase in blood guanidine for some time after the injection.…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand,it was also found that a thyreoparathyreodectomy in dogs also causes hypoglycemia and depletion of glycogen deposits in the liver and no glycosuria (11).Extirpation of three parathyroid glands caused a reduction of absorption of dextrose given by mouth or subcutaneously.Normalisation of calcium serum level by administration of calcium lactate resulted in normalisation of blood sugar content (12), while it had been shown that ammonia elimination into the urine was increased (13). At the same time Burns and Sharpe demonstrated a marked increase of guanidine in the urine and blood of parathyreidectomized dogs and in the urine of children with idiopathic tetany (14).On the basis of the assumption that parathyroids are involved in glucose metabolism,Watanabe first studied the effect of subcutaneous guanidine administration on rabbit blood sugar levels and on urinary excretion of glucose and of ammonia (15)(16)(17)(18).He administered guanidine hydrochloride subcutaneously into rabbits which were kept without food and water after administration and several blood glucose tests were performed after the start of the experiments.A decrease of glucose serum level was observed, wich was paralleled by a deterioration of general conditions until death occurred.…”
Section: History Of Biguanide: From the First Animal Experiments To T...mentioning
confidence: 99%